2014
DOI: 10.1161/circulationaha.114.010400
|View full text |Cite
|
Sign up to set email alerts
|

Early Structural Valve Deterioration of Mitroflow Aortic Bioprosthesis

Abstract: Early SVD is frequent in Mitroflow bioprosthesis (models 12A/LX), especially for small sizes (19 and 21 mm), and reduces overall survival. An unpredictable accelerated pattern of SVD constitutes a life-threatening condition. In view of the large number of Mitroflow valves implanted worldwide, one can expect an epidemic of SVD and valve-related deaths, which represents a major public health issue, especially in the elderly. Hence, a close follow-up with yearly echocardiography after Mitroflow implantation is ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 181 publications
(36 citation statements)
references
References 33 publications
0
35
0
1
Order By: Relevance
“…Porcine bioprostheses (Hancock II) have also demonstrated long-term durability in patients aged 60 years or older 16 while an accelerated pattern of SVD was observed with the Mitroflow prosthesis in approximately one-third of patients. 19 A study of 430 patients treated with a stentless bioprosthesis reported freedom from reoperation in 91.0% and 75.0% at 10 and 15 years, and freedom from reoperation for SVD in 95.9% and 82.3%, respectively. 17 Notably, outcomes vary with different surgical bioprostheses as demonstrated in recent post-market surveillance of 43 782 valves in England and Wales.…”
Section: Long-term Outcomes Of Bioprosthetic Valves In the Aortic Posmentioning
confidence: 99%
“…Porcine bioprostheses (Hancock II) have also demonstrated long-term durability in patients aged 60 years or older 16 while an accelerated pattern of SVD was observed with the Mitroflow prosthesis in approximately one-third of patients. 19 A study of 430 patients treated with a stentless bioprosthesis reported freedom from reoperation in 91.0% and 75.0% at 10 and 15 years, and freedom from reoperation for SVD in 95.9% and 82.3%, respectively. 17 Notably, outcomes vary with different surgical bioprostheses as demonstrated in recent post-market surveillance of 43 782 valves in England and Wales.…”
Section: Long-term Outcomes Of Bioprosthetic Valves In the Aortic Posmentioning
confidence: 99%
“…4-6, 22 Early failure, however, is not rare. 23 The potential for earlier failure of surgical valves is evidenced by a relatively short median time to therapy in the global VIV registry of only 9 years (IQR, 6-12 years). 14 Mechanisms of failure include stenosis (due to calcification, or less commonly due to pannus or thrombosis) and regurgitation (due to wear and tear, calcification, or infection).…”
mentioning
confidence: 99%
“…Early degeneration or high gradient across a bioprosthesis in elderly patients has been rarely reported [4]. Structural valve deterioration includes changes intrinsic to the valve like wear, calcification, leaflet tear, and stent creep.…”
Section: Discussionmentioning
confidence: 99%